2022
DOI: 10.1093/eurpub/ckac115
|View full text |Cite
|
Sign up to set email alerts
|

Price minimizing behaviours by smokers in Europe (2006–20): evidence from the International Tobacco Control Project

Abstract: Background Effectiveness of tobacco taxation can be undermined through smokers applying price-minimizing behaviours rather than quitting or reducing consumption. Common price-minimizing strategies are buying cheaper tobacco [discount brands or roll-your-own (RYO) tobacco], bulk buying and cross-border purchasing. This study analyses trends in and factors associated with such behaviours in four European countries from 2006 to 2020. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is not surprising that this is the least popular strategy, since it is the one which requires the most effort: low-taxed sales outlets are uncommon in the Netherlands, and require time and money to travel to. In contrast, bulk buying and switching to a cheaper product can be done at almost every point of sale [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that this is the least popular strategy, since it is the one which requires the most effort: low-taxed sales outlets are uncommon in the Netherlands, and require time and money to travel to. In contrast, bulk buying and switching to a cheaper product can be done at almost every point of sale [29].…”
Section: Discussionmentioning
confidence: 99%
“…Both nicotine dependence and having made a previous quit attempt are associated with smoking cessation [24][25][26][27]. Nicotine dependence is also associated with other behaviours such as smoking less or use of price-minimising strategies as prices increase [28,29]. Nicotine dependence was measured by the heaviness of smoking index (HSI), a six-point scale that cumulates a categorised measure of cigarettes per day (1-10 cigarettes = 0 points, 11-20 = 1 point, 21-30 = 2 points, 31 or more = 3 points) and time to first cigarette (within 5 min = 3 points, 6-30 min = 2 points, 31 min or later = 1 point) [30].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Existing research has identified demographic groups who are at greater risk for persistent tobacco use. These include individuals who are socioeconomically disadvantaged, have lower levels of education, experience poorer mental health, identify as sexual and/or gender minorities or belong to racial and/or ethnic minorities (19)(20)(21)(22)(23). In the sociomedical context, these can be interpreted as expressions of health inequity.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Another study examined trends in price-minimizing behaviors between 2006 and 2020, and found that the use of these behaviors by Dutch FM smokers ranged from 7.4% to 26.4%—depending on per year and type of price-minimizing behavior. 26 …”
Section: Discussionmentioning
confidence: 99%